Translation and adaptation of the person-centered maternity care scale to a Persian-speaking population: a confirmatory factor analysis - Mansoureh Jamshidimanesh; Nafiseh Mohammadkhani (BMC, 2024)
Abstract Background Recognized as the most exhaustive multidimensional evaluation of women's person-centered experiences during childbirth, the Person-Centered Maternity Care (PCMC) Scale offers domain-specific insights into facets of care. This instrument has yet to be translated into Persian. Hence, this study purposed to translate and ascertain the reliability and validity of a Persian version of the PCMC scale for postpartum women in Iran. Methods A cross-sectional study was facilitated at multiple comprehensive health centers within Tehran, Iran, from February 2022 until July 2022. Postpartum women within seven days after childbirth who were referred to selected comprehensive health centers for newborn thyroid screening were conveniently sampled. The validation process for the questionnaire utilized confirmatory factor analysis (CFA), while it gauged convergent validity via factor loads, average variance extracted (AVE), along with composite reliability (CR). Discriminant credibility was evaluated utilizing HTMT alongside the Fornell-Larcker Criteria. Data analysis procedures were conducted through IBM SPSS Statistics for Windows Version 16 and SMART PLS Statistics for Windows Version 4.0.9.9. Results All the items were within the acceptable range of factor loading, except for questions 3 of the facility and 6 of dignity, which were removed from the model. The AVE values for all the variables were above 0.50, and the CR values were above 0.78, indicating convergent validity. On the horizontal loading table, all of the indicators met the conditions. Additionally, the findings validate that the HTMT indicator associated with all constructs remained below 0.9, which confirms divergent relevance about the survey tool under consideration. The composite reliability values also indicated good overall reliability for all the constructs, ranging from 0.78 to 0.91. Conclusions The results of the present study indicate that the Persian version of the PCMC is a reliable and valid tool for measuring person-centered maternity care in Persian-speaking populations.